1990
DOI: 10.1128/iai.58.9.2834-2839.1990
|View full text |Cite
|
Sign up to set email alerts
|

Survival and antigenic profile of irradiated malarial sporozoites in infected liver cells

Abstract: Exoerythrocytic (EE) stages of Plasmodium berghei derived from irradiated sporozoites were cultured in vitro in HepG2 cells. They synthesized several antigens, predominantly but not exclusively those expressed by normal early erythrocytic schizonts. After invasion, over half the intracellular sporozoites, both normal and irradiated, appeared to die. After 24 h, in marked contrast to the normal parasites, EE parasites derived from irradiated sporozoites continued to break open, shedding their antigens into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…However, more recent studies carried out in parallel under in vivo and in vitro conditions have shown in both humans and rodents that protection depends on the abilities of irradiated sporozoites to penetrate hepatocytes and, further, to transform into uninucleate liver trophozoites (14). The indication that persistent liver form parasites are required to induce protection (14,38,46) was confirmed recently (34,44).…”
mentioning
confidence: 77%
“…However, more recent studies carried out in parallel under in vivo and in vitro conditions have shown in both humans and rodents that protection depends on the abilities of irradiated sporozoites to penetrate hepatocytes and, further, to transform into uninucleate liver trophozoites (14). The indication that persistent liver form parasites are required to induce protection (14,38,46) was confirmed recently (34,44).…”
mentioning
confidence: 77%
“…Nevertheless, the partial development of intranuclear parasites in vivo may participate in the development of immune responses against Plasmodium pre‐erythrocytic stages. In this regard, the partial EEF development resulting from infection by radiation‐attenuated (Suhrbier et al ., 1990; Silvie et al ., 2002) or genetically attenuated (van Dijk et al ., 2005; Mueller et al ., 2005a,b) sporozoites is associated with the induction of protective immune responses against subsequent sporozoite challenge (Nussenzweig et al ., 1967; Hoffman et al ., 2002; van Dijk et al ., 2005; Mueller et al ., 2005a,b).…”
Section: Discussionmentioning
confidence: 99%
“…This development entails a sequential change in the proteins expressed, sporozoite surface proteins are progressively downregulated, liver stage specific proteins are expressed and merozoite proteins upregulated. [16][17][18][19] Schizont development takes from 3-11 days dependent upon parasite species, in which time some parasite proteins are inexplicably processed on proteasomes in the host cell cytoplasm, and presented by class I MHC on the hepatocyte surface, identifying infected cells for attack by both CD4 and CD8 T cells, and killing by cytokine mediated mechanisms. These processes remain very poorly understood, and clearly require further study if pre-erythrocytic vaccines targeting finite numbers of proteins/epitopes are to achieve their maximal potential.…”
Section: The Parasites' Life Cycles and Anti-parasitic Vaccinesmentioning
confidence: 99%